ChemInform Abstract: Copper(II)‐Catalyzed Reactions of Dimethylformamide with Phenylacetonitrile and Sulfur to Form N, N‐Dimethylthioamides. Issue 15 (15th April 2014) - Qu, Yanyang; Li, Zhengkai; Xiang, Haifeng; Zhou, Xiangge
Abstract The selective preparation of phenylethanethioamides and thiobenzamides is achieved via copper‐catalyzed reaction of phenylacetonitriles, DMF and sulfur.